2021
DOI: 10.3390/nu13020598
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and Peptide YY in Association with Depressive Symptoms and Eating Behaviours in Adolescents across the Weight Spectrum: From Anorexia Nervosa to Obesity

Abstract: Neuropeptide Y (NPY) and peptide YY (PYY) are involved in metabolic regulation. The purpose of the study was to assess the serum levels of NPY and PYY in adolescents with anorexia nervosa (AN) or obesity (OB), as well as in a healthy control group (CG). The effects of potential confounders on their concentrations were also analysed. Eighty-nine adolescents were included in this study (AN = 30, OB = 30, and CG = 29). Anthropometric measurements and psychometric assessment of depressive symptoms, eating behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 108 publications
0
4
1
Order By: Relevance
“…Elevated PYY levels have also been reported in critically ill patients, particularly in patients with food intolerance ( 36 ). The PYY levels were 25.49 ± 9.79 pg/mL among adolescents with anorexia nervosa and 18.46 ± 9.81 pg/mL in healthy adolescents, which is a much lower concentration than in our study, but this difference may occur due to technical differences in the tests used for the analysis ( 37 ). There were no differences in PYY levels between females and males with CF, as well as homozygous and heterozygous for ΔF508.…”
Section: Discussioncontrasting
confidence: 74%
“…Elevated PYY levels have also been reported in critically ill patients, particularly in patients with food intolerance ( 36 ). The PYY levels were 25.49 ± 9.79 pg/mL among adolescents with anorexia nervosa and 18.46 ± 9.81 pg/mL in healthy adolescents, which is a much lower concentration than in our study, but this difference may occur due to technical differences in the tests used for the analysis ( 37 ). There were no differences in PYY levels between females and males with CF, as well as homozygous and heterozygous for ΔF508.…”
Section: Discussioncontrasting
confidence: 74%
“…The levels of NPY in normal weight was (3.08±0.02 pg/ml), (Table 5) which was higher than both of overweight and obese with three classes (I, II, III), (Figure 1). These studies had reported similar results (Milewicz et al, 2000), (Baltazi et al, 2011), (Tyszkiewicz-Nwafor et al, 2021). Studies who showing that negative correlation between BMI and NPY were observed in obese and serum NPY levels were significantly lower in obese.…”
Section: Discussionmentioning
confidence: 56%
“…Disruptions in hormonal balance have been associated with various eating disorder 9 11 . Numerous studies have been conducted to elucidate the pathogenesis of ED, particularly involvement of “appetite-regulating hormones”, such as peptide YY (PYY) and acylated-ghrelin 12 , 13 . PYY is involved in energy intake through gastrointestinal digestion 14 , 15 , where it inhibits the orexigenic neuropeptide Y neurons in the hypothalamus as part of its central anorexigenic function 14 .…”
Section: Introductionmentioning
confidence: 99%